Binding of PDZ domains to the carboxy terminus of inducible nitric oxide synthase boosts electron transfer and NO synthesis. Issue 17 (14th July 2015) - Aicart-Ramos, Clara; Rodríguez-Crespo, Ignacio
Abstract : iNOS lacks any phosphorylatable residue at its C‐terminus despite displaying a 25‐residue extension known to block electron transfer and activity. We report that C‐terminal deletions of iNOS increased the cytochrome c reduction rate. Moreover, the interaction of the iNOS C‐terminus with the PDZ domains of EBP50 or CAP70 resulted not only in augmented reductase activity and greater NO synthesis but also anticipated the formation of the air‐stable semiquinone generated after NADPH addition. Hence, the C‐terminus of iNOS regulates the activity of the enzyme, albeit, unlike nNOS and eNOS, displacement of the autoinhibitory element occurs upon binding to proteins with PDZ domains. Abstract : The C‐terminus of iNOS is an inhibitory element that regulates NO synthesis. Binding of PDZ domains to the C‐terminus of iNOS releases this autoinhibitory module. Subcellular transport and localization of iNOS concomitantly result in activation.